Understanding the home range characteristics of the first naturally bred pair of crested ibis(Nipponia nippon) released into the natural habitat - Soodong Lee; Chunghyeon Oh; Bonggyo Cho; Youngsub Han (BMC Zoology)
Abstract Background The crested ibis, a species that relies on wetland ecosystems for survival, was once found throughout East Asia but has declined to near extinction in Korea, Russia, and Japan, except China. Artificial propagation of seven individuals found in Yangxian, Shaanxi Province, China has resulted in a stable population. Furthermore, South Korea and Japan are working on restoring populations through donations from China. Artificial propagation began in 2008, and in 2019, 40 individuals born between 2014 and 2018 were released into the natural habitat for the first time. We conducted this study to analyze the habitat environment, home range, and habitat usage patterns of a 2016-born male and a 2017-born female who attempted to reproduce naturally for the first time. Results After forming a breeding pair on April 3, 2020, the pair made two breeding attempts, built a nest in Pinus densiflora, and succeeded in hatching the chicks, but failed to raise them. The home range analysis showed that the area was 1.777–2.425 km² for MCP 100%, and 0.347–2.085 km² for 95% KDE. Meanwhile, the core habitat ranged from 0.007 to 0.296 km² (KDE 50%), indicating differences depending on the time of year and the individual being studied. Breeding pairs were estimated to spend over 50% of their recorded occurrences within 50 m during nesting for incubation, resting, and other activities. They mainly used in paddy fields, but from April to June, when onions and garlic were growing, they searched for food in fields, cemeteries, reservoirs, and other areas. Conclusion Breeding pairs have increasingly become more active near the nest, and Changnyeong-gun, where they were released, has large agricultural land suitable for crested ibis habitat. However, there is a problem that during the breeding season from April to June, most paddy fields are maintained as garlic and onion fields, which are then converted back for rice cultivation from May to June through double-cropping. Accordingly, for stable laying and rearing, it is necessary to contemplate how to maintain rice paddies, which serve as feeding grounds in the core habitats.